Distribution, spectral characteristics, and seasonal variation of dissolved organic matter in the northern Beibu Gulf, South China Sea - Zhu, Zuhao; Wei, Huihua; Guan, Yao; Zhang, Li; Jia, Renming; Sun, Pengfei; Yang, Yang; Zhang, Zhen; Zhang, Qiufeng (Frontiers in Marine Science, 2022)
Dissolved organic matter (DOM) in the land–ocean interface plays a critical role in the global carbon cycle, yet its dynamic is not well understood. Dissolved organic carbon (DOC) in the northern Beibu Gulf was measured seasonally from April 2020 to January 2021. Chromophoric and fluorescent DOM (CDOM and FDOM) were synchronously characterized by absorption and fluorescence spectroscopy. Three fluorescent components were identified from 597 samples using parallel factor analysis, including two humic-like and one protein-like component. DOC displays a significant seasonality with the average level being highest in summer (177 μmol/L) and lowest in winter (107 μmol/L). CDOM and FDOM levels in summer are also higher than those in winter. Although the variation ranges of DOC, CDOM, and FDOM in surface water are generally greater than in bottom water, the difference between the two layers is statistically insignificant. River discharge and anthropogenic input are important external sources of DOM in the low-salinity nearshore waters (i.e., estuaries and coast), whereas DOM in offshore waters is mainly produced by in situ biological activity. The mixing behavior of DOM in the northern Beibu Gulf varies spatially but minimally on a seasonal scale. Two distinct conservative mixing behaviors of DOC, CDOM, and humic-like FDOM occur in the nearshore waters from Tieshangang Bay and excluding Tieshangang Bay, respectively. The removal of protein-like FDOM along the salinity gradient and the negative correlation between protein-like FDOM intensity and apparent oxygen utilization are pronounced in the nearshore waters excluding Tieshangang Bay, jointly indicating that oxygen is consumed by microbial communities. In contrast, a net addition of DOC occurs in the high-salinity offshore waters, whereas the CDOM and humic-like FDOM undergoes quasi-conservative mixing. Overall, this study reveals notable spatial and seasonal variations in the concentration, source, and mixing of DOM at the land–ocean interface and highlights the importance of sources and processes in shaping the amount and composition of DOM exported to the ocean margin.